The Relationship Between Reserve Items and Exchange Rate in Malaysia: Evidence from Non-linear Model - Seyed Alireza, Seyed Ahmadian; Rosita, Hamdan; Jerome, Kueh (Human Resource Management Academic Research Society, 2021)
The objectives of this study are first, to examine a nonlinear long-run relationship between exchange rate and reserve and related item in Malaysia. Second, to examine the causal relationship between exchange rate, reserve and related item, money supply, interest rate, foreign direct investment, and price in Malaysia. Third, to forecast the relationship between exchange rate, reserve and related item, money supply, interest rate, foreign direct investment, and price in Malaysia for the next 50 years. To achieve our objective, we employed the nonlinear autoregressive distributed lag model (NARDL), Toda Yamamoto causality test and variance decomposition. We utilize a time series dataset from 1982 to 2018. We find reserve items are significant to have a negative relationship with exchange rate. However, it limits to only a decrease in reserve items will encourage the Ringgit to be depreciated. On the other hand, reserve items are expected to influence more in exchange rate fluctuation in the next 50 years. On the other hand, reserve items are significant to cause FDI inflow in Malaysia.